Evaluation of Achievement of Health Nutrition Program Indicators Mother and Child Towards the Healthy Family Index in Kalibobo District, Nabire District - Melince Degei; Nur Susan Iriyanti Ibrahim; Bau Kanag (International Journal of Medicine and Health, 2024)
Maternal and child health issues are still a serious concern for the government today. The high maternal, infant and toddler mortality rates make KIA a top priority in the Ministry's program.Health problems at the Kalibobo Health Center are still the center of attention where in 2023 there were 2 child deaths including nutritional problems. Objective: To analyze the achievement of indicators of the nutritional health program, mothers and children against the healthy family index in Kalibobo Village, Nabire Regency. Method: Observational research is descriptive. Using the Community Diagnosis (Needs Assessment) method with a cross-sectional approach. The sample size120 familiesusing cluster random sampling method. The interview results were collected and data reduction, data presentation and conclusion drawing were carried out. Results: ANC examination 74% (national target 95%), complete basic immunization 89% (national target 90%), infants aged 0-6 months who received exclusive breastfeeding 67% (national target 60%) and toddlers whose growth was monitored 75% (national target 85%). Conclusion: Based on the 4 indicators evaluated, there are 2 indicators that can be said to be successful, namely the achievement of toddlers who received complete basic immunization and infants aged 0-6 months who received exclusive breastfeeding. Suggestion: to establish cross-sector cooperation in the community so that community knowledge, attitudes, and behavior can be better in utilizing existing health services, especially maternal and child health services.